DIPLOMASI BAHASA DAN BUDAYA INDONESIA MELALUI KEGIATAN EKSTRAKURIKULER KELAS BUDAYA DI UNIVERSITAS SOUSSE TUNISIA - Eko Widianto (Universitas Sultan Ageng Tirtayasa, 2018)
This study aimed to describe an Indonesian language and cultural diplomatic process in Tunisia, introduction of Wayang Kulit to the student, introduction of Blangkon and Tenun Troso to the student, introduction of Tembang Jawa (Javanese Traditional Song) to the student, and introduction of Roro Jonggrang story to the student in University of Sousse, Tunisia. The data were collected via study case method. A researcher took a part in the even to collect an analyse the research data. A diplomatic mission to introduce language and culture of Indonesia could be showed by Kelas Budaya. Kelas Budaya was an extracurricular even to introduce a variety of Indonesian culture. This program became one of the ISOL (BIPA)’s support to promote an Indonesian culture. A student in University of Sousse interested to this program as an additional even exclude the formal class. Therefore, Kelas Budaya had a good implication to support diplomatic mission in the University of Sousse, Tunisia.